Adaptation Strategy And of Topo Da’a Remote Indigenous Communities Survivability to Climate Change in Their Settlement Environment (Case Study: Lekatu Da’a Topo Settlement in Central Sulawesi Province) - Amar, Amar; Masiming, Zulfitriah; Butudoka, Zubair; Mulyati, Ahda (Devotion : Journal of Research and Community Service, 2024)
Topo Da’a is one of sub-ethnic of Kaili tribe in Central Sulawesi, Indonesia. This Isolated Traditional Community or Komunitas Adat Terpencil (KAT) originally is nomadic people who live in Kamalisi mountain forest area. Generally, this society live in mountain area either in highland area, mountain slope, or lowland area. Topo Da’a Lekatu settlement is the only settlement of Topo Da’a that located in Palu city administrative region. This settlement is in lowland area that near from central area of Palu city. Aim of this study is to know how adaptation strategy and community survival ability against climate change environment around their living area from inside the mountain forest area with low temperature then live in lowland area the near the center of the city with high temperature. Qualitative method with phenomenological approach applied in this research. Data collection is purposive sampling with snowball sampling technique. Data analysis is inductive with three steps of selection or reduction, which are phenomenological reduction, eidetic reduction, and transcendental reduction. The research results found that the main factors of survival were economic factors and customs. Apart from that, the settlement location is close to schools and markets. Meanwhile, the adaptation strategy is to adjust to different climates, by creating relaxing or gathering space outside their house and sometimes they sleep in the farm that located on the mountain.